Isolated Cerebral Mucormycosis in an Immunocompetent Patient—A Case Report - Reddy, R. Hari Kishore; Raju, Subodh (Indian Journal of Neurosurgery, 2015)
Isolated Infection of central nervous system by the family Mucoraceae is a rare but life-threatening infection. We present a case of isolated cerebral mucormycosis in a 53-year-old immunocompetent woman without any rhinoorbital focus. She underwent excision biopsy followed by treatment with amphotericin B, resulting in resolution of symptoms clinically and the lesion radiologically.
Keywords: isolated; cerebral mucormycosis; immunocompetent; fungal infection; amphotericin B